Physical and Mechanical Characteristics Analysis of Partition Composite Board Made of Coconut Shell Material - Mega Safana; Suparno Suparno; Rangga Alif Faresta (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to examine the effect of the thickness of coconut shell composite board on elasticity, sound absorption, water absorption, and density. The elasticity test was conducted using the tensilon RTF2350 machine at the Faculty of Mechanical Engineering and the sound absorption test was conducted using the sound level meter GM1352 at the Faculty of Science and Mathematics of the State University of Yogyakarta. The thickness of the composite board was varied, and its elasticity was measured using the tensilon RTF2350 machine, the sound absorption measurement was determined using a sound level meter with a sound source from a sound generator with a frequency of 1000Hz and intensity of 20 dB, while the thickness was varied. The elastic modulus decreased with the increase in partition thickness, sound absorption decreased with the increase in partition thickness, and water absorption increased with the increase in partition thickness. Water absorption was determined by submerging the partition into distilled water for 30 seconds and observing the mass before and after immersion into the water.